Inverse system design based on the volterra modeling of a parametric loudspeaker system - Ji, Wei (2013)
Parametric loudspeaker systems have been widely used for projecting high directional audible sound beams. However, the nonlinear interaction among primary waves also generates harmonics, which distort the desired signal and degrade the sound quality. In order to investigate this inherent nonlinear mechanism, a baseband distortion model is developed from nonlinear system identification using an adaptive Volterra filter. For the conventional double-sideband amplitude modulation (DSBAM) technique, it is found that the harmonic distortion is largely attributed to the second harmonic. The adaptation results derived from both simulation and measurement indicate that the first few coefficients of the second-order kernel are dominant. Based on the Volterra model, a pth-order inverse system is designed to compensate the harmonic distortions present in the demodulated signal. Simulation and measurement results demonstrate that the harmonic distortion can be greatly reduced to an acceptable level when the inverse system is introduced with a suitable recursive order.